Ultrastructural and Cytological Studies on Mycosphaerella pinodes Infection of the Model Legume Medicago truncatula - Suzuki, Tomoko; Maeda, Aya; Hirose, Masaya; Ichinose, Yuki; Shiraishi, Tomonori; Toyoda, Kazuhiro (Frontiers in Plant Science, 2017)
Ascochyta (Mycosphaerella) blight on cultivated peas is primarily caused by infection through asexual spores (pycnospores) of Mycosphaerella pinodes (Berk. et Blox.) Vestergren [recently renamed Peyronellaea pinodes (Berk. & A. Bloxam) Aveskamp, Gruyter & Verkley]. Using a recently developed model pathosystem involving Medicago truncatula and M. pinodes strain OMP-1, we examined the histology and ultrastructure of early infection events and fungal development including penetration by appressoria, vegetative growth of infection hyphae, and host responses. On the susceptible ecotype R108-1, pycnospores germinated and grew over the surface of the epidermis, then formed an appressoria and penetrated the cuticle. Beneath the cuticle, the infection peg expanded into a hyphae that grew within the outer wall of the epidermis. Subsequently, the hyphae penetrated down within mesophyll cells and proliferated vigorously, eventually, forming asexual fruiting bodies (pycnidia). In contrast, successful penetration and subsequent growth of infection hyphae were considerably restricted in the ecotype Caliph. Detected by its reaction with cerium chloride (CeCl3) to produce electron-dense cerium perhydroxides in transmission electron micrographs, hydrogen peroxide (H2O2) accumulated in epidermal and mesophyll cells of Caliph challenged with pyconospores of M. pinodes. This intracellular localization was confirmed by energy-dispersive X-ray (EDX) spectroscopy. Our observations thus indicate that the oxidative burst reaction leading to the generation of reactive oxygen species is associated with a local host defense response in Caliph, since no clear H2O2 accumulation was detectable in susceptible R108-1. Indeed, aberrant hyphae such as intrahyphal hyphae and dead hyphae, probably due to a local defense elicited by the fungus, were abundant in Caliph but not in R108-1. Our results on the cellular interactions between the fungus and host cells provide additional insights to understand foliar infection by M. pinodes on cultivated peas.